The Level of Psychological Hardiness among Female Teachers of Children with Learning Disabilities in the Sultanate of Oman: Descriptive Study - Al-Muqbali, Rahma bint Abdullah; Al-Fawair, Ahmed Muhammad Jalal (Journal of Educational and Psychological Sciences, 2020)
This study aims at identifying the level of psychological hardiness for the female teachers of students with learning disabilities in the Sultanate of Oman. The study sample consists of (88) female teachers of students with learning difficulties. Psychological hardiness instrument developed by Mekhemar (2002) was used. The study results showed that the level of psychological hardness for female teachers of students with learning difficulties in the Sultanate of Oman was moderate. In addition, the study results showed that there was significant difference in the level of psychological hardiness among the teachers of students with learning difficulties due to specialization in favor of the first field, while there was no significant difference in the level of psychological hardiness due to experiences.